2019
DOI: 10.7554/elife.42746
|View full text |Cite
|
Sign up to set email alerts
|

State transitions in the substantia nigra reticulata predict the onset of motor deficits in models of progressive dopamine depletion in mice

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder whose cardinal motor symptoms are attributed to dysfunction of basal ganglia circuits under conditions of low dopamine. Despite well-established physiological criteria to define basal ganglia dysfunction, correlations between individual parameters and motor symptoms are often weak, challenging their predictive validity and causal contributions to behavior. One limitation is that basal ganglia pathophysiology is studied only at end-stages of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 98 publications
(152 reference statements)
5
70
0
Order By: Relevance
“…To confirm this in another manner, we rebuilt the models using the same cross-validated 179 training and testing sets as above using only a single parameter at a time, or using all of the 180 parameters except oscillations. The first four parameters fall outside (FR) or on the edge (CV 181 performs better than any individual parameter ( Figure 4d), confirming results seen previously 183 (Willard et al, 2019). However, the model built using only oscillations as a predictor is, on 184 average, better than any other model including the combined parameter model, providing further 185 evidence that other physiological parameters are not additionally informative when oscillations 186 are considered.…”
Section: Of Dysfunction 139supporting
confidence: 71%
See 4 more Smart Citations
“…To confirm this in another manner, we rebuilt the models using the same cross-validated 179 training and testing sets as above using only a single parameter at a time, or using all of the 180 parameters except oscillations. The first four parameters fall outside (FR) or on the edge (CV 181 performs better than any individual parameter ( Figure 4d), confirming results seen previously 183 (Willard et al, 2019). However, the model built using only oscillations as a predictor is, on 184 average, better than any other model including the combined parameter model, providing further 185 evidence that other physiological parameters are not additionally informative when oscillations 186 are considered.…”
Section: Of Dysfunction 139supporting
confidence: 71%
“…Hammond et al, 2007; Jenkinson & Brown, 2011). Here, we demonstrate dopamine loss and 321 PD-like symptoms in mice without the presence of beta oscillations, and we have previously 322 demonstrated their absence in LFP signals in awake mice as well(Willard et al, 2019). Indeed, 323to our knowledge, no study has demonstrated the presence of beta oscillations in mouse 324 models of PD.…”
mentioning
confidence: 67%
See 3 more Smart Citations